Land Officer Role in Development of Sharing Collective Rights to Heirs with Mental Disability - Muhammad Einan Nabil (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Land Deed Making Official/PPAT is an official who is given the authority to make an authentic deed that can be trusted. The division of inheritance for the heirs can be the right of each of the holders of the joint rights based on the Deed of Sharing the Joint Rights made by the PPAT. The purpose of this research is to find out the role of PPAT in making APHB and what to do if one of the heirs is incompetent the process after APHB is made along with examples from APHB. This study uses a normative juridical approach, The data analysis method used is a qualitative analysis method with descriptive analytical research specifications, data collection methods with literature study, data sources used are secondary data. Based on the results of research and discussion: 1) PPAT has an important role, namely the General Official who helps the parties to achieve their wishes, prepares and registers a transfer of rights to share rights with a land right at the Land Office, and has the authority to make APHB as an authentic deed; 2) When an heir is incompetent due to a mental disability, the heir is represented by the custodian because people with mental disabilities are usually not able to carry out activities like people in general; 3)PPAT is obliged to register the transfer of rights to the local Land Office after the APHB is made; 4) Sample APBH made by PPAT. It is recommended that PPAT must master the law of inheritance in carrying out their duties. A custodian must be responsible for all legal actions committed by the holder. The government, especially the National Land Agency, is expected to further socialize all regulations regarding land, especially regarding Land Registration.